The association between the Mediterranean Diet and the prime diet quality score and new-diagnosed irritable bowel syndrome: a matched case-control study - Baghdadi, Ghazal; Feyzpour, Marzieh; Shahrokhi, Seyedeh Atiye; Amiri, Roksaneh; Rahimlou, Mehran (Frontiers in Medicine, 2025)
BackgroundIrritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disorder with multifactorial etiology. Dietary patterns, including the Mediterranean Diet (Med-Diet) and the Prime Diet Quality Score (PDQS), may play a role in IBS risk. This study examined the association between adherence to the Med-Diet and PDQS and new-diagnosed IBS in an Iranian population.MethodsA matched case-control study was conducted on 170 newly diagnosed IBS patients and 340 age- and sex-matched controls recruited from outpatient clinics in Zanjan, Iran. Dietary intake was assessed using a semiquantitative food frequency questionnaire. The Med-Diet score and PDQS were calculated, with higher scores indicating better diet quality. Conditional logistic regression was used to determine the odds of IBS across quartiles of Med-Diet and PDQS, adjusting for sociodemographic and clinical factors.ResultsHigher adherence to the Med-Diet was associated with 51% lower odds of IBS (OR: 0.49; 95% CI: 0.30–0.73, P < 0.001) in the highest quartile compared to the lowest. Similarly, participants in the highest PDQS quartile showed a significantly 59% lower odds of IBS (OR: 0.41; 95% CI: 0.26–0.51, P < 0.001) compared to the lowest quartile. Both associations remained significant after adjusting for potential confounders, including total energy intake. These findings highlight the potential clinical relevance of dietary quality in IBS prevention.ConclusionHigher adherence to the Med-Diet and a higher PDQS were both inversely associated with IBS risk. Specifically, individuals with higher Med-Diet scores and higher PDQS scores had a lower risk of developing IBS compared to those with lower adherence or scores. These findings suggest a potential role of these dietary patterns in modulating IBS risk, although causal relationships cannot be established from this study.